Economic benefit and social impact derived by a food loss prevention strategy in the vegetable sector: A spatial and temporal analysis at the regional level - Tonini, Pietro; Odina, Pere Muñoz; Orsini, Francesco; Durany, Xavier Gabarrell (Frontiers in Sustainable Food Systems, 2022)
Reduction of food loss in the horticultural sector is critical to simultaneously support the transition towards a diet with higher consumption of vegetables and the achievement of policy goals aimed at halving the quantity of wastage by 2030. However, the lack of precise information and the presence of multiple interconnected factors makes it difficult to assess the potential socioeconomic benefits and therefore the decision-making process. Based on these issues, the aim of the research was to provide different quantitative socioeconomic evidence that can complementarily be adopted to facilitate the elaboration of food loss reduction strategies. A case study approach has been selected to give a clear interpretation of the scale of the problem to speed up the response at a political and business level. The quantitative evidence highlights the most critical products, provinces, and months where food prevention strategies should be prioritized based on economic and social variables. The results helped to quantify the economic impact of food loss and explore the potential contrast between the policy of reducing food losses and the ability of the population to increase the consumption of a specific vegetable.